2021
DOI: 10.3389/fphar.2021.738121
|View full text |Cite
|
Sign up to set email alerts
|

Renal ROCK Activation and Its Pharmacological Inhibition in Patients With Diabetes

Abstract: Rho-associated coiled-coil-containing protein kinase (ROCK) is a serine/threonine kinase with essential roles in cytoskeletal functions. Substantial evidence implicates ROCK as a critical regulator in the inception and progression of diabetic nephropathy through a mechanism involving mesangial fibrosis, podocyte apoptosis, and endothelial inflammation. Despite these experimental observations, human data is lacking. Here we show that the phosphorylated form of myosin phosphatase targeting subunit 1 (MYPT1), a R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The only currently approved treatment for DN is the blockade of the renin–angiotensin system (RAS), which appeared to be effective 20 years ago. However, this treatment has various limitations and does not result in significant benefits for patients with DN [ 26 , 27 ]. Therefore, identifying potential new therapies and molecular targets is of immense practical importance.…”
Section: Discussionmentioning
confidence: 99%
“…The only currently approved treatment for DN is the blockade of the renin–angiotensin system (RAS), which appeared to be effective 20 years ago. However, this treatment has various limitations and does not result in significant benefits for patients with DN [ 26 , 27 ]. Therefore, identifying potential new therapies and molecular targets is of immense practical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these mentioned drugs, the dipeptidyl peptidase 4 inhibitors are also a therapeutic approach currently recommended in the new KDIGO guidelines ( Kidney Disease: Improving Global Outcomes Diabetes Work Group, 2020 ). In addition, new anti-inflammatory therapies and metabolic modulators, such as JAK/STAT, Rho-kinase and Sirtuin-3 inhibitors, peptide N-Acetyl-Seryl-Aspartyl-Proline, glycolysis inhibitors, and mineralocorticoid receptor antagonists, have been postulated as potential drugs in DN due to the preclinical evidence, showing their renoprotective role or even their ability to reverse established renal damage ( Hashimoto et al, 2010 ; Bakris et al, 2020 ; Locatelli et al, 2020 ; Opazo-Ríos et al, 2020b ; Srivastava et al, 2020 ; Matoba et al, 2021 ). Growing evidence in all these mentioned studies has shown that the reno-protective effects of these drugs, at least, in part, may be due to the regulation of epithelial and endothelial-to-mesenchymal transition (EMT and EndoMT) in the progression of DN.…”
Section: Introductionmentioning
confidence: 99%
“…Fasudil also ameliorated albuminuria and glomerular hypertrophy in DN mice by downregulating HIF-1α expression ( Matoba et al, 2013 ). Furthermore, the application of fasudil can reduce proteinuria and improve renal prognosis by inhibiting ROCK activity in diabetic patients ( Matoba et al, 2021 ). Studies have also shown that fasudil can inhibit NF-κB nuclear translocation and TGF-β1 expression in STZ-induced diabetic rats ( Xie et al, 2013 ).…”
Section: Pyroptosis and Drugs In Diabetic Nephropathymentioning
confidence: 99%